2014
DOI: 10.4103/0975-7406.129175
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and determinants of medication adherence among hypertensive patients attended National Health Service Hospital, Sunderland

Abstract: Background:Hypertension is a silent killer, a time bomb in both the developed and developing nations of the world. It is one of the most significant risk factors for cardiovascular morbidity and mortality resulting from target-organ damage to blood vessels in the heart, brain, kidney and eyes. Adherence to long-term therapy for chronic illnesses like hypertension is an important tool to enhance the effectiveness of pharmacotherapy.Objective:The two objectives of this study were to evaluate the extent and reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
5
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 29 publications
4
45
5
3
Order By: Relevance
“…The finding is lower than the studies conducted in Maritime Canada (77.0% [26], Pakistan(77.0%) [27], Singapore (75.2%) [28] and in Sunderland (79%) [29]. This difference could be due to difference in socio-demographic characteristics and health care facilities among this study and the comparison studies.…”
Section: Discussioncontrasting
confidence: 78%
“…The finding is lower than the studies conducted in Maritime Canada (77.0% [26], Pakistan(77.0%) [27], Singapore (75.2%) [28] and in Sunderland (79%) [29]. This difference could be due to difference in socio-demographic characteristics and health care facilities among this study and the comparison studies.…”
Section: Discussioncontrasting
confidence: 78%
“…13 Three other studies at Sunder lands, Ethiopia and Pakistan showed better adherence rates of 79% ,64.6% and 77% respectively. [18][19][20] Another study in South India with 516 patients, prevalence of poor adherence to hypertension medications was 25.58% which was higher when compared to present study (18.7%). 10 Those were conducted at hospital settings unlike our study which was in a community setting.…”
Section: Discussioncontrasting
confidence: 51%
“…23 Compliance from study using Morisky Medication adherence Scale in a study in Sunderland was found to be 79%. 24 A slightly lower level of compliance (55.5%) was reported in a study in Ethiopia using the MMAS-8 scale. 25 Ajayi et al reported a prevalence of 44.7% from a study in Nigeria using MMAS-4 scale for measuring adherence.…”
Section: Discussionmentioning
confidence: 99%